The Relationship Between Physical Activity And Peak Height Velocity In Children Aged 9 – 11 Years (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
The purpose of this research was to determine the relationship between physical activity and the age of PHV in children aged 9-11 years. The method used in this research is a test survey with data collection techniques using questionnaires and measurement tests. The population in this research is SSB Tugumuda athletes and grade 4 students at SDN Karangjati 04. The samples were taken from as many as 29 boys from SSB Tugumuda and 23 boys from SDN Karangjati 04 aged 9-11 years. The sampling technique uses purposive sampling. The data analysis technique in this research used the Pearson bivariate correlation test. The results showed that 1) The level of physical activity of 1 child (1.9%) had a "low" level of activity, as many as 18 children (34.6%) had physical activity said to be "sufficient", 32 children (61.5%) with a "high" level of physical activity and 1 child (1.9%) had a "very high" level of activity, 3) The average age of PHV in 52 respondents was 14.02 years. It was concluded that there was a relationship between physical activity to the age of PHV in the 2 groups.